2016
DOI: 10.1093/mnras/stw360
|View full text |Cite
|
Sign up to set email alerts
|

Advective and diffusive cosmic ray transport in galactic haloes

Abstract: We present 1D cosmic ray transport models, numerically solving equations of pure advection and diffusion for the electrons and calculating synchrotron emission spectra. We find that for exponential halo magnetic field distributions advection leads to approximately exponential radio continuum intensity profiles, whereas diffusion leads to profiles that can be better approximated by a Gaussian function. Accordingly, the vertical radio spectral profiles for advection are approximately linear, whereas for diffusio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 72 publications
5
80
1
1
Order By: Relevance
“…If streaming dominated the cosmic ray electron transport, the convolution kernel is expected to be an exponential. This is justified by the results of Heesen et al (2016), who found that within their 1D cosmic ray transport model advection leads to approximately exponential radio continuum intensity profiles, whereas diffusion leads to profiles that can be better approximated by Gaussian functions. Since advection and streaming are formally similar (the outflow velocity has to be replaced by the Alfvén velocity), the effect of streaming can be approximated by a convolution with an exponential kernel.…”
Section: Methodsmentioning
confidence: 76%
“…If streaming dominated the cosmic ray electron transport, the convolution kernel is expected to be an exponential. This is justified by the results of Heesen et al (2016), who found that within their 1D cosmic ray transport model advection leads to approximately exponential radio continuum intensity profiles, whereas diffusion leads to profiles that can be better approximated by Gaussian functions. Since advection and streaming are formally similar (the outflow velocity has to be replaced by the Alfvén velocity), the effect of streaming can be approximated by a convolution with an exponential kernel.…”
Section: Methodsmentioning
confidence: 76%
“…We fitted the intensity profiles with 1D cosmic ray transport models for advection and diffusion using SPINNAKER (Heesen et al 2016). In order to calculate the radio spectral indices that are required as input, we used a 1570 MHz map from L-band observations with the Karl G. Jansky Very Large Array (JVLA), combined from the B, C, and D array (Schmidt et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown observationally (Dahlem et al 1995;Heesen et al 2009) that the diffusion coefficient in the z direction is several times lower than the radial component. Heesen et al (2016), using 1D cosmic ray electron transport models and Australia Telescope Compact Array observations of two edge-on galaxies, found that the cosmic ray transport in the halo of NGC 7090 is advection dominated with a velocity of approximately 150 km s −1 , while NGC 7462 is diffusion dominated with a diffusion coefficient of D = 3.0 × 10 28 E 0.5…”
Section: Discussionmentioning
confidence: 99%